THE EFFECT OF THIRD-PARTY FUNDS, FINANCING, AND EQUITY ON NET INCOME BANK MUAMALAT INDONESIA - Nurhayati, Nurhayati; Puteh, Anwar; M Nur, Mukhlish; Hafizh, Muhammad (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2024)
Third party funds, financing, and equity are important factors in some of the factors that influence net income, which take money from the public and then rechannel it into society. This research is aimed at knowing the impact Third-party fund, Financing, and Equity to Net income with research subject Bank Muamalat Indonesian period 2014-2023. This study employs multiple linier regression analysis and quantitative approaches. The study object is presented as published financial reports from Bank Muamalat Indonesia (2014-2023). And analyzed with the Eviews 12 statistical tool. The outcome of the study demonstrate Third-Party Funds a positive and significant effect on Net Income because the t-count value for Third-Party Funds > t-table is 2,9206 > 2,0280 and the significant value for Third-Party Funds < 0,05 is 0,0060 < 0,05. The result of Financing has a positive and insignificant impact on Net Income this is shown by the t-count value for Financing < t-table is 0,6558 < 2,0280 and the significant value for Financing > 0,05 is 0,5161 > 0,05. The results of Equity a negative and insignificant impact on Net Income because the t-count value of Equity < t-table is -0,1850 < 2,0280 and significant value for Equity > 0,05 is 0,8542 > 0,05. Simultaneously Third-party Funds, Financing, and Equity the effect Net Income, this is proven by the value significant F test 0,0007 < 0,05. The value of coefficient of determination (R2) is 0,3198 or 31,98%, which means that the Third-Party Funds, Financing, and Equity variables the effect net Income by 31.98%, while other factors not included in this study account for 68,02% of the explanation.